Profile of cognitive deficits among children residing in areas with high ambient air pollution in Odisha - Kulumina Dash; Pratap Kumar Jena; Jigyansa Ipsita Pattnaik; Sayali Mishra; Jayaprakash Russell Ravan (Industrial Psychiatry Journal)
Background: The detrimental effects of air pollution on human health, particularly among vulnerable populations such as children, have raised concerns globally. While prior research has explored the association between air pollution and cognitive impairments, it is poorly studied in the Indian population. Aim: This study aims to specifically profile the cognitive deficits experienced by children residing in areas with high ambient particulate matter air pollution (PM10 and PM2.5) in Odisha. Material and Methods: A total of 30 children aged 6–8 years from Kalinga Nagar, Odisha were sampled, and their cognitive functions covering domains such as memory, attention, IQ, executive function, verbal skills, vocabulary, visuospatial ability, and processing speed and accuracy were assessed using the Malin’s Intelligence Scale for Indian Children (MISIC). Results: The mean full-scale IQ of the children was 84 as per MISIC, indicating that on average, the children’s IQ falls below the normal range. Specifically, the children showed lower performance in tests assessing attention, working memory, general knowledge acquisition, mathematical skills, vocabulary, and spatial reasoning. Conclusion: Six- to eight-year-old children residing in areas with high ambient particulate pollution exhibited lower cognitive abilities, including deficits in attention, working memory, mathematical skills, vocabulary, and visual-spatial processing.